2007
DOI: 10.1177/1545968306296966
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Balance, Disability, and Recovery After Stroke: Predictive Validity of the Brunel Balance Assessment

Abstract: Initial balance disability is a strong predictor of function and recovery after stroke. These results demonstrate the predictive validity of the BBA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
0
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 39 publications
1
69
0
14
Order By: Relevance
“…Kim and Park (2013) reported that balance impairment leads to dependency in activities of daily living of stroke patients. Tyson et al (2007) reported that balance ability affect performance in ADL of stroke patients. In addition, according to a previous study that examined the effect of cognitive impairment on functional limitation post-stroke, cognitive impairment caused by a stroke can have far-reaching consequences on ADL (Zinn et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim and Park (2013) reported that balance impairment leads to dependency in activities of daily living of stroke patients. Tyson et al (2007) reported that balance ability affect performance in ADL of stroke patients. In addition, according to a previous study that examined the effect of cognitive impairment on functional limitation post-stroke, cognitive impairment caused by a stroke can have far-reaching consequences on ADL (Zinn et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have identified balance ability as important risk factor for independent ADL in stroke patients (Tyson et al 2007;Kim and Park 2013). Kim and Park (2013) reported that balance impairment leads to dependency in activities of daily living of stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with post-stroke hemiparesis have balance deficits and natural decreases in muscle strength and age-related endurance [3,4]. Specifically, stroke patients usually place more weight unilaterally [5,6] and find balancing when standing/ sitting difficult [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improvements in rehabilitation outcomes and goal setting are important for stroke patients 6,7) . To set suitable therapeutic goals and develop effective treatment plans, predictions need to be made about patients' expected degree of recovery 8) . Selection of assessments is an important process, but it is difficult because of the variability in causes, symptoms, severity, and the possibility of spontaneous recovery following stroke 9) .…”
Section: Introductionmentioning
confidence: 99%